Experience in developing an innovation in view of its scientific verification and the product placement on the market - Žegarac, Nikola P. (Vojnotehnički glasnik / Military Technical Courier, 2016)
The paper presents an innovative device for dismantling and assembling parts of not-easily detachable assemblies of mechanical and electrical plants for on-site overhaul. The novelty is that the device offers fast and efficient dismantling and assembling of parts, without the possibility of damage. It is easy to use and easy to carry. It is used for all types of plants and higher levels of overhaul in field conditions. This quality device has been in the market for 4 years. The device is expected to be used over the next 10 years, and probably longer. Many years of experience in solving maintenance and repair problems resulted in this device for dismantling and assembly of mechanical and electrical assemblies. Many assemblies could not be dismantled and assembled in field conditions. The new device enabled developing a new technology of on-site overhaul and new methods of organization work and overhaul execution. It took only six months from an idea to its implementation due to producer’s extensive experience in these and similar jobs. This innovative device is sold with the contractual obligations regarding the protection of the confidentiality of its construction and application. The device is in the process of obtaining patent rights from the Intellectual Property Office in Belgrade, and after that it will be filled as an international patent application to the PCT.